Impact of Using E-Filing, E-Billing, and Trust in Authorities on Individual Taxpayer Compliance (A study at the Pratama Kediri Tax Service Office) - Asterina, Talasa Cucha; Saleh, Khairul -; Widyanti, Dika Vivi (Admisi dan Bisnis, 2024)
Efficient tax management and increasing taxpayer compliance are key challenges in modern tax administration. Therefore, the Directorate General of Taxes strives to enhance the number of taxpayers complying with reporting Annual Tax Returns (SPT) and paying tax bills on time. This research investigates the effects of using e-Filing and e-Billing systems, as well as trust in authority, on personal taxpayer compliance. The use of e-Filing and e-Billing expedites the tax submission and payment processes, thereby fostering taxpayer compliance. This study was conducted at the Primary Tax Service Office in Kediri using descriptive analysis method. The population studied consists of 121,291 employees in Kediri, with a sample size of 107 respondents selected through non- probability purposive sampling. Data analysis employed classical assumption tests, hypothesis testing using t-test, F-test, coefficient of determination, and multiple linear regression analysis, facilitated by IBM SPSS Statistics 25 software.